(untitled) (Journal of the College of Basic Education, 2024)
The research aims to show the attention of the hadith scholars to the hadith of the Prophet, may God’s prayers and peace be upon him and his family, as they distinguished his words from the words of others so that the words of the revelation of prophecy would not be confused with others. This distinction came through extrapolation of the prophetic hadiths, collecting and probing the paths, then examining them and determining whether they were unique or not, and all of that in order to They determine whether some of the narrators included their words with the words of the Prophet, may God’s prayers and peace be upon him and his family, or not, and then they set some rules and regulations for knowing the included hadith. They presented many examples and divisions that indicate their keen interest in this matter